Pengaruh Tekanan Gas pada Proses Thermal Spray Aluminium (TSA) terhadap Keausan dan Morfologi Pada Baja ST 60 - Bram Ihza Pramudya; Sri Hastuti; Herru Santosa Budiono (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
The use of steel in industry continues to increase until now making it the material most often used in transportation equipment such as cars, ships and trains. Steel is used in the transportation construction industry, steel materials are often used for railway axle construction. Hardness values ​​were taken using the Vickers micro test, and wear using a taber abrasive tool. Based on this background, research will be carried out "The Effect of Gas Pressure in the Thermal Spray Aluminum (TSA) Process on the Hardness and Wear Resistance of ST-60 Steel". This research uses medium carbon steel material with a coating process via TSA. The resulting layer is expected to have better hardness and wear values. The research method used in this research is the experimental method. The experimental method is a method used to test the effect of a treatment on the object under study by comparing when treatment is carried out and without treatment. This research carried out tests on 15 test objects. The substrate material used is ST 60 steel. In the thermal spray process three variations of gas pressure are used, namely 3 Bar, 6 Bar, and 9 Bar. Hardness values ​​were taken using the Vickers micro test, and wear using a taber abrasive tool. The highest average value of layer wear occurred at a pressure variation of 4 Bar with a layer thickness of 0.00859 mm2/kg. The lowest average layer wear value occurred at a pressure variation of 3 Bar with a wear value of 0.00729 mm2/kg. Meanwhile, based on coating layer thickness testing, the highest average layer thickness value occurred at a pressure variation of 4 Bar with a layer thickness of 423.854 µm. The lowest average layer thickness value occurred at a pressure variation of 3 Bar with a layer thickness of 241.505 µm.